Ascl1 phospho-status regulates neuronal differentiation in a Xenopus developmental model of neuroblastoma - Luke A. Wylie; Laura J. A. Hardwick; Tatiana D. Papkovskaia; Carol J. Thiele; Anna Philpott (The Company of Biologists, 2015)
Neuroblastoma (NB), although rare, accounts for 15% of all paediatric cancer mortality. Unusual among cancers, NBs lack a consistent set of gene mutations and, excluding large-scale chromosomal rearrangements, the genome seems to be largely intact. Indeed, many interesting features of NB suggest that it has little in common with adult solid tumours but instead has characteristics of a developmental disorder. NB arises overwhelmingly in infants under 2 years of age during a specific window of development and, histologically, NB bears striking similarity to undifferentiated neuroblasts of the sympathetic nervous system, its likely cells of origin. Hence, NB could be considered a disease of development arising when neuroblasts of the sympathetic nervous system fail to undergo proper differentiation, but instead are maintained precociously as progenitors with the potential for acquiring further mutations eventually resulting in tumour formation. To explore this possibility, we require a robust and flexible developmental model to investigate the differentiation of NB's presumptive cell of origin. Here, we use Xenopus frog embryos to characterise the differentiation of anteroventral noradrenergic (AVNA) cells, cells derived from the neural crest. We find that these cells share many characteristics with their mammalian developmental counterparts, and also with NB cells. We find that the transcriptional regulator Ascl1 is expressed transiently in normal AVNA cell differentiation but its expression is aberrantly maintained in NB cells, where it is largely phosphorylated on multiple sites. We show that Ascl1's ability to induce differentiation of AVNA cells is inhibited by its multi-site phosphorylation at serine-proline motifs, whereas overexpression of cyclin-dependent kinases (CDKs) and MYCN inhibit wild-type Ascl1-driven AVNA differentiation, but not differentiation driven by a phospho-mutant form of Ascl1. This suggests that the maintenance of ASCL1 in its multiply phosphorylated state might prevent terminal differentiation in NB, which could offer new approaches for differentiation therapy in NB.